CIPP evaluation model in the educational evaluation: A literature study - Suri, Sufyan; Hariyati, Nunuk (CAHAYA PENDIDIKAN, 2024)
Evaluation in education is an important component that must be carried out to ensure that educational goals can be achieved effectively and efficiently. The evaluation model that is widely used in educational evaluation activities is the CIPP evaluation model developed by Stufflebeam. The CIPP model is a comprehensive evaluation model with four evaluation aspects, namely context, input, process, and product. This research is qualitative research with a literature study research method. This research aims to identify important components used in educational evaluation using the CIPP model. Data collection was carried out by collecting supporting literature from books and research journals from various national and international sources related to educational evaluation using the CIPP evaluation model. Data was analyzed by using content analysis techniques. The research results show that the CIPP model is a model that is widely used in educational program evaluation activities. Context evaluation to assess educational program objectives. Input evaluation to identify readiness and resources to support program implementation. Process evaluation to analyze program implementation and obstacles. Product evaluation to see the educational program's achievements.